Productivity Analysis of Micro Scale Tempe Processing Businesses in South Konawe Regency - Nasrullah, Nasrullah; Rianda, La; Herdhiansyah, Dhian; Asriani, Asriani (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
This research aims to analyze the productivity of micro-scale tempeh processing businesses in South Konawe Regency. Determining the research location was carried out purposively. The sampling method used in the research is the census method technique, where the samples used in this research are the Micro A, Micro B, Micro C, Micro D, Micro E, and Micro F tempeh businesses. Data collection was carried out using questionnaires, interviews. , documents and libraries. The analysis used is analysis of labor productivity, production productivity, income and trade system margins. The results of the research show that the labor productivity of micro-scale tempe businesses that have very good consecutive criteria is Micro B and C. The production productivity of micro-scale tempe businesses is Micro A, B, C, D and E. The income of tempe businesses is the highest. The highest micro scale in one production is the micro B tempeh industry with a value of Rp. 3,069,000.